An X-ray computed tomography analysis of damage induced by thermal cycling in non-crimp fabric composites. (January 2022) - Lizarralde, I.; Sapountzi, E.; Bénéthuilière, T.; Sket, F.; González, C.
Abstract: In this work, the micro-crack formation and propagation mechanisms are characterized by X-ray computed tomography (XCT) in non-crimp fabric (NCF) laminates produced by resin transfer moulding (RTM) and subjected to thermal cycling between − 55 °C and 72 °C. The low crimped textile structure has comparable in-plane mechanical properties to their traditional unidirectional angle-ply laminates. However, the presence of the stitching thread induces the generation and progression of damage in the form of matrix cracks triggered by the temperature drop. In this study, matrix cracks are extracted from X-ray computed tomography volumes, using machine learning (ML) algorithms, which helps to deliver robust and reliable crack segmentation as well as geometrical features of the damage shape, size, spatial distribution and density. This information allows understanding damage progression.